Edukasi Hukum tentang Bahaya Penyebaran Hoaks dan Dampak Kerugian pada UMKM - Amiruddin Islami MQ. Baba; Adi Papa Jefrianto Bondi; Anabella Alya Wardhani; Ahmad Saleh; Aditya Murdiman; Erma Hari Alijana (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The Community Service Program (PKM) activity entitled “Legal Education on the Dangers of Hoax Dissemination and Its Economic Impact on MSMEs” aims to enhance public understanding and legal awareness, particularly among Micro, Small, and Medium Enterprises (MSMEs), in using social media wisely and responsibly by addressing the main issue of low digital literacy and limited understanding of the legal consequences of spreading hoaxes, which can result in social and economic losses, including decreased consumer trust in MSMEs. The program was implemented through stages of data collection, training, mentoring, and evaluation, with educational materials focusing on the understanding of hoaxes, their forms of dissemination, legal implications, and the economic losses they may cause, while mentoring ensured participants could apply this knowledge in their daily lives. The results indicate an improvement in public awareness of the dangers of hoaxes, increased ability to verify information, and stronger legal awareness in the use of social media, as well as the development of critical and responsible attitudes in sharing information; despite challenges related to varying levels of participant understanding, the program overall had a positive impact on enhancing digital literacy, legal awareness, and the sustainability of MSME businesses.